THE READINESS IN IMPLEMENTING VALUE ENGINEERING ON INFRASTRUCTURES DEVELOPMENT OVER THE NANGGROE ACEH DARUSSALAM - FAUZAN (NIM 25005033), M.
Nanggroe Aceh Darussalam (NAD) is the area that most seriously affected by earthquake and tsunami waves disasters on December 26th 2004. The natural disasters have devastated almost all of the community living aspects, including its infrastructures. There is estimation that rehabilitating and reconstructing NAD’s infrastructures require at least 30 Trillion Rupiah funding. Some of the constrains faced in implementing the rehabilitations and reconstructions are: serious land devastations, more complex and more tight planning criteria, the limitations of resources and short program execution time schedule. Anticipating these constrains requires an effective and efficient management technique. In the USA, and some of other advanced countries, the adoption of Value Engineering (VE), documented satisfactorily results as management tools. It was documented that the VE implementation were robust in saving over 25% large scale projects’ budget all over the USA. Considering the urgent need of the region to adopt better management systems, and based on the positive results documented in VE implementations in USA, initial steps in mapping the potential readiness to implement VE over NAD should be taken. These steps will involve analyzing the prerequisite factors to implement VE method, and observing the readiness of its implementation over the infrastructures development in NAD. The former step will be performed by studying the successful implementation principles of the VE method in USA and other countries and adapted them into variables and indicators of study. These variables and indicators should be built under the assumptions that the construction service communities in NAD have no familiarity with the VE method, in such a way that we need intermediating or intervening variables to study the readiness in implementing VE through supporting principles such as value improvement policy. Based on these variables and indicators, questionnaires could be set and distributed subsequently to three groups of construction service community’s samples in NAD. 25 of 35 distributed questionnaires were filled. The collected data have been processed by descriptive statistic method through percentages and scales and Analytical Hierarchical Process (AHP) to observe the importance level of the variables analyzed. The results suggested that the prerequisite factors in implementing VE as formulated in form of these variables and indicators are observed in NAD. The prerequisites factors achievement levels based on samples are: consultants designs: 69,31%, contractors: 66,2% and owners: 62,23%. These results suggest that, NAD is ready to implement VE in its infrastructure development. Due to the results are only based on the analyses of respondents’ opinions through questionnaires they filled, the actual facts should be explored and elaborate further, to gain more comprehensive analysis of readiness of NAD’s construction service community in implementing VE.